Uji Psikometrik Skala University Student Engagement Inventory (USEI) Versi Bahasa Indonesia: Validitas dan Reliabilitas pada Mahasiswa di Indonesia - Kartika Prananto (Universitas Kristen Maranatha, 2025)
The issue of student engagement in higher education has received increasing attention in recent decades due to its important role in enhancing students’ motivation, academic success, and psychological well-being. Measuring engagement allows higher education institutions to identify areas for improvement and design interventions to enhance the learning experience. This study aims to adapt the University Student Engagement Inventory (USEI) for students in Bandung City, to make it relevant to the local cultural and educational context. The USEI instrument, developed by João Maroco (2016), measures three dimensions of engagement and has been translated and tested for content validity by five experts, resulting in s-cvi of 0.72 (relevance), 0.96 (importance), and 0.84 (clarity), indicating good validity. This instrument was subsequently tested among 150 active students in Bandung City through an online platform, with a construct reliability result of 0.824—indicating good reliability. Confirmatory factor analysis (CFA) analysis on 11 USEI items showed the results of χ2/df = 1.170, p-value = 0.009, RMSEA = 0.063, GFI = 0.928, CFI = 0.947, and TLI = 0.929, indicating that the CFA model is valid. Further research is suggested to involve larger and more diverse samples from various universities and faculties in Bandung City.